High Lubricity Meets Load Capacity: Cartilage Mimicking Bilayer Structure by Brushing Up Stiff Hydrogels from Subsurface. (2nd August 2020) - Rong, Mingming; Liu, Hui; Scaraggi, Michele; Bai, Yanyan; Bao, Luyao; Ma, Shuanhong; Ma, Zhengfeng; Cai, Meirong; Dini, Daniele; Zhou, Feng
Abstract: Natural articular cartilage has ultralow friction even at high squeezing pressure. Biomimicking cartilage with soft materials has been and remains a grand challenge in the fields of materials science and engineering. Inspired by the unique structural features of the articular cartilage, as well as by its remarkable lubrication mechanisms dictated by the properties of the superficial layers, a novel archetype of cartilage‐mimicking bilayer material by robustly entangling thick hydrophilic polyelectrolyte brushes into the subsurface of a stiff hydrogel substrate is developed. The topmost soft polymer layer provides effective aqueous lubrication, whereas the stiffer hydrogel layer used as a substrate delivers the load‐bearing capacity. Their synergy is capable of attaining low friction coefficients (order 0.010) under heavily loaded conditions (order 10 MPa contact pressure) in water environment, a performance incredibly close to that of natural articular cartilage. The bioinspired material can maintain low friction even when subjected to 50k reciprocating cycles under high contact pressure, with almost no wear observed on the sliding track. These findings are theoretically explained and compounded by multiscale simulations used to shed light on the mechanisms responsible for this remarkable performance. This work opens innovative technology routes for developing cartilage‐mimicking ultralow friction soft materials. Abstract : A cartilage mimicking bilayer material is engineered, which is capable of attaining low friction coefficient (order 0.010) under heavily loaded conditions (order of 10 MPa contact pressure). The construct can maintain low friction when subjected to 50k reciprocating cycles under high contact pressure with almost no surface wear in water environment, a performance matching that of natural articular cartilage.